2007
DOI: 10.1016/j.bbadis.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ferroportin1, hephaestin and ceruloplasmin in rat heart

Abstract: Iron-mediated injury plays an important role in a number of heart disorders. Studies on heart iron are therefore crucial for understanding the causes of excessive heart iron. Heart cells have the ability to accumulate transferrin-bound-iron via the transferrin receptor and non-transferrin-bound-iron probably via the L-type Ca2+ channel and the divalent metal transporter1. However, little is known about the mechanisms of iron export in the heart cells. Here, we investigated expression of iron exporters includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 47 publications
4
30
0
Order By: Relevance
“…We found dramatically increased cardiac iron comparable to the nutritional iron overloaded mice and suggests that Cp plays an important role in mobilizing iron from the heart. A recent study found expression of both Hp and Cp in the heart but only Cp was responsive to iron levels (Qian et al 2007). As has been previously noted, the Cp -/-mouse has elevated spleen and liver iron.…”
Section: Hematology and Tissue Iron Levels In 1 Year Old Micementioning
confidence: 96%
“…We found dramatically increased cardiac iron comparable to the nutritional iron overloaded mice and suggests that Cp plays an important role in mobilizing iron from the heart. A recent study found expression of both Hp and Cp in the heart but only Cp was responsive to iron levels (Qian et al 2007). As has been previously noted, the Cp -/-mouse has elevated spleen and liver iron.…”
Section: Hematology and Tissue Iron Levels In 1 Year Old Micementioning
confidence: 96%
“…Recently, we investigated expression of iron exporters including ferroportin 1 (Fpn1), ceruloplasmin (CP) and hephaestin (Heph) and provided evidence for their existence in the heart [8]. We also demonstrated that iron has a significant effect on expression of Fpn1 and CP.…”
Section: Introductionmentioning
confidence: 95%
“…For this reason, the iron levels in tissues must be tightly regulated. The increased iron and iron-mediated injury have been proposed to play an important role in the development of a number of heart disorders, including heart ischemia-reperfusion injury, iron-overload cardiomyopathy, acute myocardial infarction and coronary heart diseases [2][3][4][5][6][7][8]. At present, it is unknown how iron increases to a pathological level in the heart under abnormal circumstances.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that iron loading increases ferroportin mRNA and protein levels in macrophages 44,45 and other cells, 3,[46][47][48][49] by acting at transcriptional 45,49 and posttranscriptional 47 levels. In addition to iron, ferroportin expression is posttranslationally mediated by hepcidin.…”
Section: Alterations In Muscle Iron Metabolism After Rhepo Administramentioning
confidence: 99%